Alternative nutritional solutions for the culture of ornamental bromélias - Vívian Tamaki; Sidnéia Maria de Paula; Catarina Carvalho Nievola; Shoey Kanashiro (O Mundo da Saúde)
Cultivating ornamental bromeliads has been considered an important strategy for their preservation, because it allows the supply of a greater amount of plants to the market, reducing the use of units proceeding from the natural environment. Generally producers use fertilizers based on different compositions of nitrogen, phosphorus and potassium. However, nutritional studies using in vitro cultivation technique have shown a satisfactory development of bromeliads as compared to other nutrients used in other techniques such as those in Murashige & Skoog (MS) and Knudson (K). The objective of this work was to verify the growth of plants of three species of ornamental bromeliads: Acanthostachys strobilaceae (Schult. f.) Klotzsch, Aechmea bromeliifolia (Rudge) Baker e Alcantarea imperialis (Carrière) Harms, gotten from the germination of seeds and fertilized with nutritional solutions based on MS and K. Plants with two months were transferred to isopor trays with Pinus rind as substratum, and were fertilized during six months with original MS and K and a dilution of half MS and half (MS/2). We examined number of leafs, stem and root axis lengths, dry and wet masses of aerial and root parts, in addition to photosynthetic pigments. We observed that the more diluted solutions (K and MS/2) were more favorable to the growth of the three bromeliads species. The highest concentrations of calcium and magnesium in K probably favored the development of the plants, indicating the important of nutritional supplements for bromeliads cultures.